2022
DOI: 10.1158/1078-0432.ccr-21-3430
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Model Based on Tumor and Immune Biomarkers to Predict Undetectable MRD and Survival Outcomes in Multiple Myeloma

Abstract: Purpose: Undetectable measurable residual disease (MRD) is a surrogate of prolonged survival in multiple myeloma. Thus, treatment individualization based on the probability of a patient achieving undetectable MRD with a singular regimen could represent a new concept toward personalized treatment, with fast assessment of its success. This has never been investigated; therefore, we sought to define a machine learning model to predict undetectable MRD at the onset of multiple myeloma. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Based on the LMR-SSIGN-MAPS model, the K-M survival analysis showed that higher LMR-SSIGN-MAPS scores were signi cantly correlated with poorer DFS in the overall cohort (P < 0.0001). Therefore, the integrated prognostic model LMR-SSIGN-MAPS was in agreement with the view that multiple markers integration can be used to provide higher accuracy and predictive e cacy [30].…”
Section: Discussionsupporting
confidence: 75%
“…Based on the LMR-SSIGN-MAPS model, the K-M survival analysis showed that higher LMR-SSIGN-MAPS scores were signi cantly correlated with poorer DFS in the overall cohort (P < 0.0001). Therefore, the integrated prognostic model LMR-SSIGN-MAPS was in agreement with the view that multiple markers integration can be used to provide higher accuracy and predictive e cacy [30].…”
Section: Discussionsupporting
confidence: 75%
“…Based on the LMR-SSIGN-MAPS model, the K-M survival analysis showed that higher LMR-SSIGN-MAPS scores were significantly correlated with poorer DFS in the overall cohort (p < 0.0001). Therefore, the integrated prognostic model LMR-SSIGN-MAPS was in agreement with the view that multiple marker integration can be used to provide higher accuracy and predictive efficacy [31]. However, certain limitations with this model warrant further discussion.…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies have demonstrated correlations between immune status and outcome following current therapies, including in long-term survivors. 26,[102][103][104][105][106] As these models continue to be refined, it is likely that we may be able to utilize immune status as a tool to select patients for specific immune therapies, as well as optimal sequencing and combinations.…”
Section: Immune Status and Implications For Immune Therapiesmentioning
confidence: 99%